Effects of strategy instruction in an efl reading comprehension course: a case study (2012)
Strategy instruction is useful in teaching contexts. This paper examines the effects of strategy instruction in an EFL reading comprehension course carried out with 26 undergraduate students at a Colombian university. As a research method, a case study was implemented. There were three instruments with which to collect data: reading comprehension tests, teacher’s field notes and self-reflection in class at the strategy instruction phase, and a learning perception questionnaire. Given that students improved in reading comprehension, it would seem that reading strategy instruction is indeed very useful. Also, it was noted that when students applied reading strategies, they became more self-confident and this in turn enhanced their motivation. Finally, when students applied the reading strategy approach, the use of dictionaries decreased considerably. La instrucción basada en estrategias es útil en los contextos de lectura. Este artículo reporta los efectos de instrucción basada en estrategias de lectura en inglés como lengua extranjera a un grupo de 26 estudiantes de enfermería de una universidad colombiana. Como método de investigación se llevó a cabo el estudio de caso. Para recolectar la información, se aplicaron tres instrumentos: pruebas de comprensión de lectura, notas de campo y la autorreflexión en clase en la fase de instrucción de estrategias, y un cuestionario de percepción de aprendizaje. Debido a que los estudiantes mejoraron en la comprensión de lectura, se concluye que la instrucción basada en estrategias de lectura parece ser beneficiosa. Se observó que cuando los estudiantes aplicaban las estrategias de lectura, mostraban mayor autoconfianza, lo cual incrementó su motivación. Además, cuando los estudiantes aplicaban el enfoque de estrategias de lectura, el uso del diccionario disminuyó considerablemente.